2017
DOI: 10.1007/978-981-10-3233-2_17
|View full text |Cite
|
Sign up to set email alerts
|

RUNX1 and CBFβ Mutations and Activities of Their Wild-Type Alleles in AML

Abstract: Mutations in RUNX1 and CBFB have long been recognized as important in hematological malignancies. Point mutations and deletions of RUNX1 are frequently found in myelodysplastic syndrome, myeloproliferative disease, and acute myeloid leukemia. Germline mutations in RUNX1 are associated with familial platelet disorder with predisposition to AML. In addition, as will be discussed in other chapters, both RUNX1 and CBFB are involved in recurrent chromosomal rearrangements in leukemia. More recently, roles for the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 113 publications
(139 reference statements)
0
6
0
Order By: Relevance
“…Entinostat has also been shown to cause differentiation and apoptosis in leukemia cells expressing the fusion gene MLL-AF9. Although this fusion protein is not known to interact with HDAC1, it does require RUNX1 expression for its leukemogenic activity (48)(49)(50). These results may imply a common role for HDAC1 in RUNX1dependent leukemia.…”
Section: Discussionmentioning
confidence: 92%
“…Entinostat has also been shown to cause differentiation and apoptosis in leukemia cells expressing the fusion gene MLL-AF9. Although this fusion protein is not known to interact with HDAC1, it does require RUNX1 expression for its leukemogenic activity (48)(49)(50). These results may imply a common role for HDAC1 in RUNX1dependent leukemia.…”
Section: Discussionmentioning
confidence: 92%
“…14 In AML, RUNX1 mutations often co-occur with mutations in FLT3, MLL-PTD, DNMT3A, ASXL1, CEBPA, NRAS, KIT, and IDH1/2. 21,22,26 Germline, monoallelic, and intragenic mutations and deletions in RUNX1 cause the highly penetrant (;40%) autosomal dominant familial platelet disorder (FPD), with a propensity to evolve into myeloid malignancy (FPD-MM). 20,[26][27][28] Previous reports showed that wild-type RUNX1 (wtRUNX1) activity is necessary to sustain leukemia caused by RUNX1-RUNXT1, CBFb-SMMHC, and MLL-ENL or MLL-AF9.…”
Section: Introductionmentioning
confidence: 99%
“…21,22,26 Germline, monoallelic, and intragenic mutations and deletions in RUNX1 cause the highly penetrant (;40%) autosomal dominant familial platelet disorder (FPD), with a propensity to evolve into myeloid malignancy (FPD-MM). 20,[26][27][28] Previous reports showed that wild-type RUNX1 (wtRUNX1) activity is necessary to sustain leukemia caused by RUNX1-RUNXT1, CBFb-SMMHC, and MLL-ENL or MLL-AF9. 26,[29][30][31] However, in AML expressing mtRUNX1, the effects of knockdown of RUNX1 have not been determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RUNX1 and CBFB genes are recurrently mutated in AML. Although a variety of mutations in RUNX1 have been described in hematologic malignancies, the only rearrangement associated with CBFB is the pericentric inversion inv(16)(p13q22), henceforth inv(16), in leukemia ( 7 9 ). The inv(16) generates the fusion gene CBFB-MYH11 , encoding the leukemia fusion protein CBFβ–SMMHC ( 10 ).…”
Section: Introductionmentioning
confidence: 99%